Synthesis and characterization of screen-printed CdS films - Kumar, V.; Sharma, D.K.; Bansal, M.K.; Dwivedi, D.K.; Sharma, T.P. (Science of sintering, 2011)
Cadmium sulphide films having energy band gap of 2.4 eV found applications in solar cells and electroluminescent devices. CdS polycrystalline films have been prepared on ultra-clean glass substrate by screen-printing technique and then sintered in air. Optimum conditions for preparing good quality screen-printed films have been found. The optical band gaps ?Eg? of the CdS films were determined from the UV transmission spectroscopy and were found to be 2.47eV. The Wurtzite structure of CdS films was confirmed by X-ray diffraction analysis. DC conductivity and activation energy of films was also measured in vacuum by two-probe technique. Kadmijum sulfidni (CdS) filmovi sa energijom procepa od 2,4 eV nalaze primenu u solarnim celijama i elektroluminescentnim aparatima. CdS polikristalni filmovi su pripremljeni na ultra-cistom staklenom substratu tehnikom sito-stampe i sinterovanjem u atmosferi vazduha. Autori su nasli optimalne uslove za pripremu kvalitetnih filmova. Opticki energetski procep ?Eg? CdS filmova odredjen je UV transmisionom spektroskopijom i iznosi 2,47 eV. Rendgenska difrakcija potvrdila je strukturu Vurcita. DC konduktivnost i energija aktivacije filmova takodje su mereni u vakuumu metodom dve probe.